Systematic Review of Educational Level and Evaluation Tools for Computational Thinking Skill - Rahim, Fanny Rahmatina; Widodo, Ari; Suhandi, Andi; Ha, Minsu (Jurnal Penelitian Pendidikan IPA, 2024)
The primary aim of this research was to conduct a systematic review on the assessment of computational thinking skills. The employed research method involved a thorough exploration of diverse databases through Google Scholar, employing the keyword "computational thinking" to retrieve pertinent articles. A total of 96 articles were chosen as research samples and subjected to analysis using content analysis techniques to scrutinize education level and evaluation tools variables. The research revealed that the education level variable was classified into four tiers: elementary school (26.17%), junior high school (29.91%), senior high school (19.63%), and college (24.30%). Simultaneously, the evaluation tool variable was categorized into four segments, comprising traditional tools (22.73%), portfolios (33.33%), interviews (15.91%), and surveys (28.03%). Computational thinking (CT) is predominantly assessed among children due to their developmental stage, fostering receptiveness to novel concepts. This facilitates the teaching of fundamental CT principles, such as programming basics, logic, and algorithms. Regarding evaluation tools, portfolios are frequently employed to assess CT as they can depict a student's proficiency in solving intricate problems, showcasing evidence of their work and completed projects for a more holistic assessment